Rapid and convenient transformation of cotton (Gossypium hirsutum L.) using in planta shoot apex via glyphosate selection - Wen-fang GUO; Kevin Yueju Wang; Nan WANG; Jun LI; Gang-qiang LI; De-hu LIU (Journal of Integrative Agriculture, 2018)
Cotton plants are recalcitrant with regards to transformation and induced regeneration. In the present study, 5-enolpyruvylshikimate-3-phosphate (EPSPS), a glyphosate resistant gene from the bacterium Agrobacterium sp. strain CP4, was introduced into an elite Bt transgenic cotton cultivar with a modified technique involving in planta Agrobacterium-mediated transformation of shoot apex. Primary transformants were initially screened using a 0.26% glyphosate spray and subsequently by PCR analysis. Five out of 4 000 transformants from T1 seeds were obtained resulting in an in planta transformation rate of 0.125%. Four homozygous lines were produced by continuous self-fertilization and both PCR-based selection and glyphosate resistance. Transgene insertion was analyzed by Southern blot analysis. Gene transcription and protein expression levels in the transgenic cotton lines were further investigated by RT-PCR, Western blot, and ELISA methods. Transgenic T3 plants were resistant to as much as 0.4% of glyphosate treatments in field trials. Our results indicate that the cotton shoot apex transformation technique which is both tissue-culture and genotype-independent would enable the exploitation of transgene technology in different cotton cultivars. Since this method does not require sterile conditions, the use of specialized growth media or the application of plant hormones, it can be conducted under the greenhouse condition.